Characterization of protein-protein interaction network in Staphylococcus aureus biofilm / Nawal Zulkiply - Zulkiply, Nawal (2023)
Staphylococcus aureus is a Gram-positive bacterium inhabiting soft tissues such as the epidermis and the nasal cavity. In chronic diseases, including osteomyelitis, endocarditis and wound infections, biofilm formation in S. aureus causes an increase in antibiotic resistance. To date, the information about the protein interaction network in S. aureus biofilm is still limited. The present work was performed to characterize S.aureus proteins and their interaction networks using in silico approach, and to identify the proteins expressed in S. aureus biofilm using tandem mass spectrometry. The preliminary characterization of protein interaction network was performed using the STRING database. Following that, S. aureus biofilm was developed in 6-well microplate and harvested at 6 h, 12 h, 18 h, and 24 h. Expression of S. aureus proteins in all biofilm stages was determined using a combination of one-dimensional SDS-PAGE and HPLC-ESI-MS/MS. Results demonstrated that a total of 430 nodes and 958 functional interactions were produced in the network. The clustering coefficient values was predicted to be 0.411. There were 421 (96%) proteins predicted as hub proteins as they showed more than 10 functional interactions with other proteins in the network. A total of 147 biological processes, 46 molecular functions, 17 cellular components and 15 biological pathways were found to be significantly (P<0.05) enriched in the protein interaction network of S. aureus. Meanwhile, six SDS-PAGE gel bands (80 kDa, 60 kDa, 58 kDa, 47 kDa, 35 kDa, 32 kDa.) were consistently expressed in 24 h S. aureus biofilm. Identified S. aureus proteins from these protein bands included L-lactate dehydrogenase (quinone), malate:quinone oxidoreductase, carbamoyl-phosphate synthase large chain, chaperone protein DnaK, serine hydroxymethyltransferase, enolase, protein translation elongation factor G, citrate synthase, isocitrate dehydrogenase, S-adenosylmethionine synthase, phosphoglycerate kinase, pyruvate kinase, L-lactate dehydrogenase, catabolite control protein A, GTPase era, elongation factor Tu, pyruvate dehydrogenase E1 component subunit alpha, and histidine--tRNA ligase which were also identified in silico.